Modernization in Environmental Change in the Novel “Baitun Nakhil” by Tarek Eltayeb: Greg Garrard’s Ecocritical Study - Nirmala, Bening Nuha; Basid, Abdul (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Modernization had a significant impact on environmental change. This change is described in the novel “Baitun Nakhil” and studied by using ecocritical theory. Ecocriticism is a way to describe the relationship between humans and nature in all cultural environments. This study aims to identify ecological narratives related to environmental change as the modernization impact in the novel “Baitun Nakhil” by Tarek Eltayeb based on Garrard’s ecocritical perspective. This study is qualitative descriptive. The data used are narratives and dialogue in the novel “Baitun Nakhil”. Data were collected by reading and note-taking techniques. Data were validated by increasing persistence, triangulation, and discussion. Data were analyzed using the Miles and Huberman method, which consists of three stages: data reduction, data presentation, and conclusion. The results of the study are the discovery of environmental change as a modernization impact in several scopes according to Garrard as follows: 1) pastoral narratives in the form of spatial and temporal distinction; 2) pollution caused by cigarettes and sirens; 3) wilderness as in mountains and forest; 4) natural disasters in the form of a snowstorm; 5) dwelling adopts the georgic concept as in Wad Al-Kababish; 6) relation between animals and human as shown by the treatment of animals and imitation of bird sounds; and 7) earth changes initiated by the plastic usage and the construction of greenhouse as conservation efforts. This study proves that modernization destroys nature due to the massive exploitation of natural resources. Conversely, modernization makes it easier to campaign and conserve nature with its sophisticated technology. Keywords: Ecocriticism, Environmental Change, Greg Garrard, Modernization, Novel